2021
DOI: 10.3389/fpsyg.2021.629050
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Awareness in Advanced Disease: A Review Update and Concept Analysis

Abstract: PurposeAlthough subjective knowledge about the prognosis of an advanced disease is extremely important for coping and treatment planning, the concept of prognostic awareness (PA) remains inconsistently defined. The aims of the scoping review were to synthesize a definition of PA from the most recent literature, describe preconditions, correlates and consequences, and suggest a conceptual model.MethodsBy using scoping review methodology, we searched the Web of Science and PubMed databases, and included publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…19 Eligible participants were recruited from outpatient medical oncology clinics in two major public Singaporean hospitals. The eligibility criteria included being: (1) ≥21 years old; (2) a Singaporean citizen/permanent resident; (3) cognitively able to provide informed consent (i.e., determined using medical records or an Abbreviated Mental Test 20 for participants ≥60 years old); (4) diagnosed with stage IV solid malignancy; (5) having an Eastern Cooperative Oncology Group performance score of ≥2. 21 The questionnaires were administered by trained interviewers in the participant's language of choice (English, Mandarin, and Malay).…”
Section: Participants and Study Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Eligible participants were recruited from outpatient medical oncology clinics in two major public Singaporean hospitals. The eligibility criteria included being: (1) ≥21 years old; (2) a Singaporean citizen/permanent resident; (3) cognitively able to provide informed consent (i.e., determined using medical records or an Abbreviated Mental Test 20 for participants ≥60 years old); (4) diagnosed with stage IV solid malignancy; (5) having an Eastern Cooperative Oncology Group performance score of ≥2. 21 The questionnaires were administered by trained interviewers in the participant's language of choice (English, Mandarin, and Malay).…”
Section: Participants and Study Settingsmentioning
confidence: 99%
“…The importance of PA has been highlighted in recent studies, with findings demonstrating associations between PA and informed decision‐making, 2 reduction in futile treatments, 3 and increased illness acceptance 4 . Despite these benefits to the patient, concerns regarding the potential negative psychological consequences following prognostic disclosure have been raised, 5 with research indicating that PA can be associated with worse patient outcomes, including anxiety, 6 depression, 7 and spiritual 8 well‐being. These results can be generally understood to be in line with the conceptual framework provided by the Prognostic Awareness Impact Scale (PAIS), which posits that prognostically aware patients, if they do not have appropriate adaptive mechanisms, can suffer negative psychological consequences 9 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Together, these 2 factors provided the perfect environment for establishing a foundation for a robust palliative care program as unplanned hospitalizations and COVID-related complications afforded many opportunities for the evaluation of prognosis and goals of care. The APRN at VEDG viewed prognostic awareness, "a patient's capacity to understand his or her prognosis and the likely illness trajectory," 18 as a crucial first step in the quest to impact patient outcomes. 2,18,19 Although certainly there are many complexities in predicting prognosis in most chronic illnesses, hospitalization related to exacerbation of diseases is an important transition point.…”
Section: Reflectionsmentioning
confidence: 99%
“…The APRN at VEDG viewed prognostic awareness, "a patient's capacity to understand his or her prognosis and the likely illness trajectory," 18 as a crucial first step in the quest to impact patient outcomes. 2,18,19 Although certainly there are many complexities in predicting prognosis in most chronic illnesses, hospitalization related to exacerbation of diseases is an important transition point. 20 The palliative APRN role at VEDG was adaptable and defined itself within the context of the hospital community.…”
Section: Reflectionsmentioning
confidence: 99%
“…A recent systematic review of the concept found that essential components include an accurate estimation of possible recovery or incurable nature, awareness of mortality, and understanding of the goals of treatment. 9 When patient prognostic awareness is rated by researchers as "more accurate, " patients are more likely to have reduced aggressiveness of care at the end of life and possibly increased depressive symptoms. [10][11][12] Other scholars have situated prognostic awareness within the construct of general health literacy, although there is likely an emotional and existential component to this aspect of self-knowledge that sets it apart.…”
mentioning
confidence: 99%